Analysis of Problem-Solving Abilities in Completing Story Problems on Combination Material Based on Student Learning Styles - Muqarrabin, Fajar; Ismaimuza, Dasa; Meinarni, Welli; Sukayasa, Sukayasa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Analysis of mathematical problem-solving abilities is a detailed observation effort of students' abilities in solving mathematical problems. Combinations in mathematics cause difficulty in understanding information and getting the main idea of sentences; therefore, knowing students' learning styles helps them choose an appropriate approach. This research aims to describe problem-solving abilities in solving combination material story problems based on the visual, auditory, and kinesthetic learning styles of class XII MIA students. This research uses qualitative methods with research instruments consisting of learning-style questionnaire sheets, test sheets, interview transcripts, and member check sheets. The research subjects consisted of a visual, an auditory, and a kinesthetic student. The research results show problem-solving abilities: 1) visual students understand problems, formulate plans, arrange to problem-solve, and review the results; 2) auditory students understand problems, prepare plans, arrange problem-solving, and review the results; 3) kinesthetic students understand problems, make plans, organize problem-solving, and not check the results. These results show that visual and auditory subjects can answer mathematical problems well and correctly. However, the kinesthetic subject is unable to solve mathematical problems. In conclusion, these results provide a detail that increases students' and teachers' awareness that kinesthetic students need extra support to improve their problem-solving ability.